Pengaruh Jumlah Pembeli Terhadap Keuntungan pada Toko Kelontong Sebelum dan Sesudah Berdirinya Mini Market di Kota Buntok Kalimantan Tengah: The Effect of Buyers Number towards Profits on Grocery Stores Before and After Establishment of Mini Market in Buntok City Central Borneo - Kurniaty, Harlina (Anterior Jurnal, 2017)
The study aims to determine the effect of the number of buyers on profits at the grocery store before and after the establishment of the Mini Market in the city of Buntok, Central Kalimantan. this type of research is descriptive quantitative research. The data used in the process can be from the interview and the distribution of questionnaires. The sample used in this study used 31 grocery stores as resource persons. The analysis was done using the Likert scale and simple regression analysis. Based on the results of research found the influence of the number of buyers to profit on grocery store before and after the establishment of the Mini Market in town buntok central Kalimantan. It can be seen from the result of simple linear regression equal to y = 3.601 + 0.876x, there is a positive relationship between the number of buyers with profit after the establishment of Mini Market to the grocery store, the calculation result of simple regression coefficient (t-test) that t count> t table (17.520 > 2.048) then H0 rejected means that there is an influence of the number of buyers with profit on the grocery store after the Mini Market stand.